The Legal System to Ensure Banking Deposits (Comparative Analytic Research) - Haval Sadeeq Ismael (Zanco Journal of Humanity Sciences)
This research deals with a modern subject in Iraq. It is related to the system of guaranteeing the banking deposits which concerns the compensation of the depositors in time of bankruptcy, or putting the bank under a curator. This will make the depositors reassured about their money and promote the trust in the banking sector especially in time of financial crisis that faces countries from time to time. The idea of insurance lies in establishing a joint- stock company which will compensate the depositors in case of insolvency of the member bank. In most countries’ membership of the company by the banks is obligatory. The joint-stock company will have its capital by the contributions of the member banks, moreover the company might make investments according to law and regulations in order to establish a good capital needs in case of compensations.